The cricket in Times Square - Selden, George (New York, N.Y. Bantam Doubleday Dell Pub., 1960)
The adventures of a country cricket who unintentionally arrives in New York and is befriended by Tucker Mouse and Harry Cat.
Keywords: William,Garth; Crickets -- Fiction; New York (City) -- Fiction; Mice -- Fiction; Cats -- Fiction